A didactical design for introducing the concepts in algebraic forms using the theory of praxeology - Nadya Syifa Utami; Sufyani Prabawanto; Nanang Priatna (Universitas Islam Negeri (UIN) Mataram, 2022)
[English]: This phenomenological study aims to thoroughly investigate the meaning of concepts in algebraic forms developed by students, both in the past learning process and in the didactical design implementation, as well as a teacher's instructional experiences as the basis for preparing a didactical design. Six seventh-grade students and a mathematics teacher participated in the study, comprising three phases: (1) analyzing students’ learning obstacles through a test and teacher’s interview, (2) preparing hypothetical learning trajectory (HLT) and didactical design based on the identification of the obstacles and in-depth interviews with the teacher, and (3) implementing the didactical design. This study revealed that students have a didactical obstacle because the teacher delivers formal definitions of algebraic form concepts followed by examples of problems. It results in epistemological obstacles, as students' understanding of the concepts is limited according to what the teacher explains. Furthermore, an HLT was developed that bridges students' arithmetic knowledge with algebra. The series of tasks were organized referring to the theory of praxeology by taking the daily-life context Let's Save. During the learning process, students use different representations, such as symbols and letters, to demonstrate the variable, reason for using a particular representation, and state the definition of a variable based on their work. The procedure was also applied to the remaining four concepts. Through the tasks, students can actively construct their conceptual understanding of the concepts in the algebraic forms. [Bahasa]: Penelitian fenomenologi ini bertujuan untuk mengkaji secara mendalam pemaknaan siswa terhadap konsep-konsep dalam bentuk aljabar, baik pada proses belajar sebelumnya maupun pada implementasi desain didaktis, serta pengalaman mengajar guru sebagai landasan dalam membuat desain didaktis. Enam siswa kelas 7 dan seorang guru matematika menjadi partisipan pada penelitian ini, yang terdiri dari tiga tahap, yaitu: (1) analisis hambatan belajar siswa melalui uji tes dan wawancara guru, (2) menyiapkan lintasan belajar hipotetik (HLT) siswa dan desain didaktis berdasarkan identifikasi hambatan belajar siswa dan wawancara mendalam dengan guru, dan (3) mengimplementasikan desain didaktis kepada siswa. Hasil penelitian ini menunjukkan bahwa siswa mengalami hambatan didaktis yang disebabkan oleh cara guru mengajar. Guru cenderung memberikan definisi formal pada konsep-konsep bentuk aljabar dilanjutkan dengan contoh-contoh soal. Hal ini mengakibatkan siswa mengalami hambatan yang bersifat epistemologis, dimana pengetahuan siswa terhadap konsep-konsep bentuk aljabar terbatas berdasarkan apa yang dijelaskan oleh guru. Kemudian, dirancang HLT yang menjembatani pengetahuan aritmatika siswa dengan aljabar. Rangkaian tugas disusun berdasarkan teori praxeology dengan mengambil konteks kehidupan sehari-hari bertema Ayo Menabung. Selama proses pembelajaran, siswa menggunakan berbagai macam representasi seperti simbol dan huruf, untuk menunjukkan variabel, mengemukakan alasan dari penggunaan representasi tertentu, dan mengungkapkan definisi variabel sesuai dengan hasil pekerjaannya. Hal ini juga berlaku pada keempat konsep lainnya. Melalui tugas yang diberikan, siswa dapat berpartisipasi aktif dalam membangun pengetahuan tentang konsep-konsep dalam bentuk aljabar.